Industrial Marketing - Mukerjee, Hory Sankar (Excel Books, 2009)
The concept of Industrial Marketing has started gaining prominence in India since the last decade. This book deals with this vast subject in a very lucid manner. The objective of this textbook is to develop an interest among the students for the subject. The book contains eighteen chapters that ideally cover a semester for an introductory course in Industrial Marketing. The salient features of this book are: v Mind power: These are articles, case studies and write ups which have been taken from the leading practitioners across the globe, and specialists of the particular areas. Each chapter of this book contains 'mind power' at the beginning and at the end. v The chapters of this textbook are highly comprehensive. The language has been kept as simple as possible with the least use of technical words or jargons. v There are case studies at the end of the book, covering the entire text, which can be used by the teachers to help the students in putting the theory to practice.